A Virtual Reality Orientation and Mobility Test for Inherited Retinal Degenerations: Testing a Proof-of-Concept After Gene Therapy - Aleman TS (Dove Medical Press, 2021)
Tomas S Aleman,1– 3 Alexander J Miller,4 Katherine H Maguire,1,2 Elena M Aleman,2 Leona W Serrano,1,2 Keli B O’Connor,1,2 Emma C Bedoukian,5 Bart P Leroy,3,6– 8 Albert M Maguire,1– 3 Jean Bennett1,2 1Scheie Eye Institute at the Perelman Center for Advanced Medicine, University of Pennsylvania, Philadelphia, PA, USA; 2Center for Advanced Retinal and Ocular Therapeutics, University of Pennsylvania, Philadelphia, PA, USA; 3Division of Ophthalmology at the Children’s Hospital of Philadelphia of the Department of Ophthalmology, University of Pennsylvania, Philadelphia, PA, USA; 4Neurology Virtual Reality Laboratory of the Department of Neurology, University of Pennsylvania, Philadelphia, PA, USA; 5Division of Human Genetics, The Children’s Hospital of Philadelphia, Philadelphia, PA, USA; 6Department of Pediatrics, Ghent University, Ghent, Belgium; 7Department of Ophthalmology, Ghent University, Ghent, Belgium; 8Center for Medical Genetics, Ghent University Hospital, Ghent, BelgiumCorrespondence: Tomas S AlemanPerelman Center for Advanced Medicine, University of Pennsylvania, 3400 Civic Center Boulevard, Philadelphia, PA, 19104, USATel +1 215 662 8676Fax +1 215 615 0527Email aleman@pennmedicine.upenn.eduPurpose: To test the ability of a virtual reality (VR) orientation and mobility (O&M) protocol to serve a measure of functional vision for patients with inherited retinal degenerations (IRDs).Methods: A VR-O&M protocol designed using a commercially available VR hardware was tested in normally sighted control subjects (n=7; ages 10– 35yo; Average 22.5yo) and patients with RPE65-associated Leber Congenital Amaurosis (n=3; ages 7– 18yo; Average 12.7yo), in two of them before and after gene therapy. Patients underwent perimetry and full-field sensitivity testing. VR-O&M parameters correlated with the visual dysfunction.Results: Visual acuities in RPE65 patients were on average worse than 20/200, dark-adapted sensitivity losses > 5 log units, and fields constricted between 20° and 40°. Before treatment, patients required ∼ 1000-fold brighter environment to navigate, had at least x4 more collisions, and were slower both to orient and navigate compared to control subjects. Improvements in cone- (by 1– 2 L.u.) and rod-mediated (by > 4 L.u.) sensitivities post-treatment led to fewer collisions (at least by half) at ∼ 100-fold dimmer luminances, and to x4 times faster navigation times.Conclusion: This study provides proof-of-concept data in support for the use of VR-O&M systems to quantify the impact that the visual dysfunction and improvement of vision following treatments has on functional vision in IRDs. The VR-O&M was useful in potentially challenging scenarios such as in pediatric patients with severe IRDs.Translational Relevance: A VR-O&M test will provide much needed flexibility, both in its deployment as well as in the possibility to test various attributes of vision that may be impacted by gene therapy in the setting of translational studies.Precis: This study provides proof-of-concept data in support for the use of a virtual reality orientation and mobility test to quantify the impact of the disease and of treatments thereof on functional vision in inherited retinal degenerations.Keywords: virtual reality, mobility, orientation, gene therapy, LCA, RPE65